Investigating techniques to reduce soft error rate under single-event-induced charge sharing - Almeida, Antonio Felipe Costa de (2014)
The interaction of radiation with integrated circuits can provoke transient faults due to the deposit of charge in sensitive nodes of transistors. Because of the decrease the size in the process technology, charge sharing between transistors placed close to each other has been more and more observed. This phenomenon can lead to multiple transient faults. Therefore, it is important to analyze the effect of multiple transient faults in integrated circuits and investigate mitigation techniques able to cope with multiple faults. This work investigates the effect known as single-event-induced charge sharing in integrated circuits. Two main techniques are analyzed to cope with this effect. First, a placement constraint methodology is proposed. This technique uses placement constraints in standard cell based circuits. The objective is to achieve a layout for which the Soft-Error Rate (SER) due charge shared at adjacent cell is reduced. A set of fault injection was performed and the results show that the SER can be minimized due to single-event-induced charge sharing in according to the layout structure. Results show that by using placement constraint, it is possible to reduce the error rate from 12.85% to 10.63% due double faults. Second, Triple Modular Redundancy (TMR) schemes with different levels of granularities limited by majority voters are analyzed under multiple faults. The TMR versions are implemented using a standard design flow based on a traditional commercial standard cell library. An extensive fault injection campaign is then performed in order to verify the softerror rate due to single-event-induced charge sharing in multiple nodes. Results show that the proposed methodology becomes crucial to find the best trade-off in area, performance and soft-error rate when TMR designs are considered under multiple upsets. Results have been evaluated in a case-study circuit Advanced Encryption Standard (AES), synthesized to 90nm Application Specific Integrated Circuit (ASIC) library, and they show that combining the two techniques, the error rate resulted from multiple faults can be minimized or masked. By using TMR with different granularities and placement constraint methodology, it is possible to reduce the error rate from 11.06% to 0.00% for double faults. A detailed study of triple, four and five multiple faults combining both techniques are also described. We also tested the TMR with different granularities in SRAM-based FPGA platform. Results show that the versions with a fine grain scheme (FGTMR) were more effectiveness in masking multiple faults, similarly to results observed in the ASICs. In summary, the main contribution of this master thesis is the investigation of charge sharing effects in ASICs and the use of a combination of techniques based on TMR redundancy and placement to improve the tolerance under multiple faults.